Moving Taylor series for solving one-dimensional one-phase Stefan problem - A. Elsaid; S.M. Helal (Alexandria Engineering Journal, 2022)
In this work, a modified form of Taylor series is proposed which we call the moving Taylor series. We prove theorems that formulate coefficients of the proposed series along with the formula of its time-derivatives. This new form of power series is applied solve one-dimensional one-phase Stefan problem which is an important model for describing heat applications with a moving boundary. Some examples are presented to demonstrate steps of the proposed technique and the results illustrate its efficiency when compared to other semi-analytic techniques.